2015
DOI: 10.1111/apa.12959
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximetry screening and prenatal diagnosis play complementary roles in reducing risks in simple transposition of the great arteries

Abstract: Pulse oximetry screening minimised the risk of discharging infants with transposition, but prenatal diagnosis would have been necessary to avoid early circulatory instability in 17% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Infants born at hospitals where pulse oximetry screening was routinely performed were diagnosed earlier than those born at hospitals that were not offering screening. The difference remained significant after excluding those detected by pulse oximetry …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Infants born at hospitals where pulse oximetry screening was routinely performed were diagnosed earlier than those born at hospitals that were not offering screening. The difference remained significant after excluding those detected by pulse oximetry …”
Section: Discussionmentioning
confidence: 92%
“…We previously reviewed infants with major Transposition of the great arteries can result in significant hypoxaemia; consequently, the sensitivity of pulse oximetry for the detection of this condition is high. 12,19 The opposite is true for AAO for which the sensitivity ranges between 20% and 40%. [20][21][22] Therefore, the maximal benefit of newborn pulse oximetry screening will likely be to those with d-TGA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In New Zealand, those with antenatally diagnosed critical CHD are delivered at the cardiac centre except in the rare case of unanticipated premature delivery. Improved antenatal detection has been predicted to reduce the risk of adverse outcome including death for d-TGA by 17% in Sweden,26 while in Holland the mortality rate decreased from 6.5% to 0% 27…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, de Wahl Granelli et al [10] found 7/66 (10.6%) false negatives, all due to aortic arch obstruction. In a study of transposition of the great arteries, there were no false negatives when pulse oximetry was used [11,12]. In the survey by Thangaratinam et al [7] there were seven studies with sensitivity of 78-100%, which implies false-negative rates of 0-12%.…”
mentioning
confidence: 99%